Testosterone, Depression, and Cognitive Impairment in Men: an Attempt at Practical Analysis - Vornyk, Borys (Health of Man, 2021)
Cognitive impairment (CI) accompanies the aging process and is manifested by difficulties with memorization, learning, concentration and decision-making, which greatly complicates the daily life of the suffering subject. In addition, medical care and social adaptation of these patients are costly and put a significant strain on the health care system. According to a forecast by G. Corona’s group, the number of people with CIs will increase significantly in the coming years, reaching 131.5 million by 2030. To date, a significant amount of researches has been conducted to uncover the mechanisms of development and risk factors of CI in order to develop effective prevention and treatment programs. Age-related decline in testosterone levels are among the potentially modified risk factors of СI. The objective: to analyze the role of testosterone in pathogenesis of cognitive impairment and depression and the possibilities of testosterone therapy to correct them. Materials and methods. Evidence was collected from the study publications and meta-analyzes exploring the role of testosterone in pathogenesis, prevention and correction of cognitive impairment and depression over the past five years and preliminary analysis of data from our own study involving 547 men with hormonal disorders. Results. Cerebral vessels are the target for the direct (via androgen receptors) and indirect (via influence on cardiovascular risk factors) action of androgens. The testosterone insufficiency is associated with both metabolic and cardiovascular disorders (hypertension, diabetes, hyperlipidemia, obesity), as well as depression and CI. Serum-free-testosterone and free testosterone index are the most sensitive biomarkers of testosterone insufficiency in patients with depression and CI. The corrective effect of testosterone therapy (TT) on depression and CI depends on their severity and levels of androgens: a clinically and statistically significant effect was registered in mild disorders with androgen deficiency. The findings of the meta-analysis do not support the use of TT for improving attention, memory (working, verbal, visual), executive function, speech, visual-motor and visual-spatial abilities in subjects with eugonadism and hypogonadism. According to preliminary analysis of the results of our study, the nature of psycho-emotional disorders is determined by the sexual constitution (SC): weak type of SC (feminine men) is associated with the higher incidence of anxiety, the strong type of SC – with propensity for depression, the middle type of SC – with aggression. Thus, testosterone, estrogens, vasopressin, and adrenaline levels should be measured in patient with aggression. Conclusions. Despite the importance of androgens for mood and cognitive functions, and their synchronous decline during the aging process, the place of TT in the prevention/ correction of whole spectrum of CIs is still unclear. It is obvious now that TT can be justified in patients with mild disorders and proven androgen signal attenuation, but in most cases has no independent meaning. Further studies to find optimal TT indications and regimes are mandatory. Когнітивні порушення (КП) супроводжують процес старіння і проявляються труднощами із запам’ятовуванням, навчанням, концентрацією уваги та прийняттям рішень, що значно ускладнює повсякденне життя суб’єкта, який ними страждає. Крім того, медичне обслуговування та соціальна адаптація таких пацієнтів є дорогими та створюють значне навантаження на систему охорони здоров’я. За прогнозом групи Г. Корони, в найближчі роки кількість людей з КП значно зросте і до 2030 року досягне 131,5 млн осіб. На сьогодні проведено значний обсяг досліджень, спрямованих на розкриття механізмів розвитку та факторів ризику КП з метою розроблення ефективних програм профілактики та лікування. Вікове зниження рівня тестостерону належить до потенційно модифікованих факторів ризику КН. Мета дослідження: аналіз ролі тестостерону в патогенезі когнітивних порушень і депресії та оцінювання можливості терапії тестостероном для їхньої корекції. Матеріали та методи. Докази були зібрані з наукових публікацій і мета-аналізів, що вивчають роль тестостерону у патогенезі, профілактиці та корекції когнітивних порушень та депресії за останні п’ять років, а також попереднього аналізу даних власного дослідження за участю 547 чоловіків із гормональними порушеннями. Результати. Судини головного мозку є мішенню для прямої (через вплив на андрогенні рецептори) та опосередкованої (через вплив на фактори серцево-судинного ризику) дії андрогенів. Недостатність тестостерону пов’язана як з метаболічними, так і серцево-судинними порушеннями (артеріальна гіпертензія, цукровий діабет, гіперліпідемія, ожиріння), а також з депресією та КП. Сироватковий вільний тестостерон та індекс вільного тестостерону є найбільш чутливими біомаркерами недостатності тестостерону у пацієнтів із депресією та КП. Коригувальна дія терапії тестостероном (ТТ) на депресію та КП залежить від їхньої вираженості та рівня андрогенів: клінічно та статистично значущий ефект зареєстрований при легких розладах на фоні андрогенного дефіциту. Результати мета-аналізу не дають підстав для використання ТТ для покращення уваги, пам’яті (робочої, вербальної, зорової), виконавчої функції, мови, зорово-моторних та зорово-просторових здібностей у суб’єктів з еугонадизмом та гіпогонадизмом. Згідно з попереднім аналізом результатів цього дослідження, характер психоемоційних порушень визначається статевою конституцією (СК): слабкий тип СК (жіночність чоловіків), що пов’язаний з більш високою частотою тривожності, сильний тип СК – зі схильністю до депресії, проміжний тип СК – з агресією. Отже, у пацієнтів з агресією слід вимірювати рівні тестостерону, естрогенів, вазопресину та адреналіну. Заключення. Незважаючи на важливість андрогенів для настрою та когнітивних функцій та синхронність їх зниження у процесі старіння, місце ТТ у профілактиці/корекції всього спектра КП залишається незрозумілим. На сьогодні очевидно, що ТТ може бути виправдана у хворих з легкими порушеннями та доведеним ослабленням андрогенного сигналу, але в більшості випадків не має самостійного значення. Необхідні подальші дослідження для пошуку оптимальних показань та режимів ТТ.